Modifikasi Bioplastik Berbasis Pati Sagu Dengan Asam Sitrat Dan Filler Microcrystalline Cellulose (MCC) - Oktaviani, Cindy; Khairat, Khairat; Bahruddin, Bahruddin (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
Bioplastic or biodegradable plastic is one of alternative replacement to conventional plastic that has the potential to harmful to the environment. One of the raw material that has the potential to be made into bioplastic is sago starch because it has ability to degraded. The general purpose of this research is to determine the characteristics of sago-based bioplastic by modified the citric acid, microcrystalline cellulose filler, plasticizer gliserol and create mathematical models of research parameters for bioplastics characteristics using statistical method. The synthesis method is casting of starch, water, filler MCC and plasticizer Glycerol with composition of filler is (15-25 % b/b), composition of plasticizer (25–35 % b/b), and composition citric acid (3-9 % b/b). The results showed that the treatment with the addition of MCC fillers, glycerol plasticizers, and citric acid are contributed to the mechanical properties produced. In the best process conditions (25% b / b MCC filler in 25% b / b glycerol plasticizer with 3% citric acid b / b) the best response value was obtained for the value of tensile strength of 9.34 MPa, elongation of 8.79%,and biodegradation of 65.68%. Keywords: bioplastics, cross-linking agents, MCC fillers, glycerol, sago starch